Analisis Kemampuan Berpikir Kritis Siswa SMP Ditinjau Dari Adversity Quotient - Rosalinda Selan; Oktovianus Mamoh; Yosepha Patricia Wua Laja (FKIP Universitas Mataram, 2023)
The aim of this study is to describe the analysis of students’ critical thinking skills from the Adversity Quotient on the mathematical system of linear equations of two variables. The type of this study is qualitative descriptive. The subjects were 28 students of class VIIIA SMPS Mimbar Budi Manufui. The instruments used were test and subject interviews. Subject interview selected 3 students with details of students of the climber type 1 student of the camper type and quiter type students. The data analysis used were tests, interviews and documents. The results of this study indicate that the type climber students are capable fulfill all indicators of students’ critical thinking to interpret, to analyze, to evaluate and to explore. While the camper students type is able to interpret, to analyze, to evaluate but they can not infer. The other result shows that quitter students just can be interpret, analyze, but they can not evaluate and infer.